Cognitive therapeutic exercise in early proprioception recovery after knee osteoarthritis surgery - Ma, Yubao; Fan, Zhijiao; Gao, Weiguang; Yu, Zihan; Ren, Muchen; Ma, Quansheng; Song, Dejun; Zhang, Lihua; Mi, Lixin (Frontiers in Rehabilitation Sciences, 2022)
Objective This research aims to explore the therapeutic effect of cognitive therapeutic exercise (CTE) in proprioception recovery after knee osteoarthritis (KOA) surgery. Methods Thirty-seven patients after KOA surgery (including 27 patients after high tibial osteotomy (HTO) and 10 patients after (TKA)) were randomly assigned to two groups. 18 subjects were assigned to the CTE group and the rest 19 subjects were assigned to the control group (no cognitive therapeutic exercise, NCTE). Proprioception training was applied to the CTE group as a cognitive therapy to improve proprioception recovery of subjects with KOA,10 minutes / time, 2 times / day, 5 days / week for 4 weeks. Except for cognitive therapy, NCTE group and CTE group had the same treatment protocols. All interventions started under the permission of the charging surgeon. In this research, we applied the positional angle reproduction method, which is a proprioception training method. The target knee flexion angles were 30°, 60°, and 90°, and all movements started from 0° of knee extension. The outcome measure is the absolute difference between the patient's actual motion angle and the target angle. Positional sensations were measured in pre-rehabilitation (Pre-Reha),2 weeks post-rehabilitation(post-Reha.2w)and 4 weeks post-rehabilitation（post-Reha.4w）. Results The CTE group had a smaller absolute difference between the patient's actual motion angle and the target angle than the control group after four weeks of treatment (P<0.05). At the end of the 2nd week, the CTE group had a smaller absolute difference than the control group at the 30° (P<0.01). At the end of the 4th week, the absolute difference of the CTE group was smaller than the control group at the 30° and 60° (P<0.05). Conclusion The joint reposition training provided for the CTE group is a painless proprioceptive training practice. This method is simple and effective, making it easy for patients to understand the purpose of training and improve patient engagement. After four weeks of rehabilitation training, the proprioception of both NCTE and CTE groups improved significantly, and the efficacy of CTE group was better than NCTE group, which provided a new idea for the early proprioception recovery of KOA patients after surgery.